Technology for Public Service Translators and Interpreters in Spain: Enhancing Employability Through Training - Vitalaru, Bianca; Pena Díaz, Carmen (Íkala, Revista de Lenguaje y Cultura, 2024)
Despite rapid technological advances and how they affect public service interpreting and translation (psit), as a subfield of translation and interpretation, very few studies focus on how technological competence affects or facilitates employability in psit. This descriptive study carried out among graduates of the University of Alcalá’s psit programme intends to fill that gap by examining the usefulness of its technology-related training. This descriptive case study sought (1) to establish which technological tools graduates had to use in their jobs and the technological requirements in the labour market for psit; (2) to establish potential differences between the T&I and the psit sectors regarding technological requirements or needs; and (3) to assess how useful the training received was. Findings show similarities in the use of sources and tools in both T&I and psit, but also differences in information mining sources, highlighting varied needs. Moreover, although computer-assisted-translation tools and machine translation are widely demanded nowadays, their use by graduates was shown to be lower than expected. This study gives critical insights for researchers, trainers, and programme designers to ensure that their syllabi encompass comprehensive content tailored to both in-house and freelance translators to increase their employability.